MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL PADA ULAR TANGGA DENGAN KARTU SOAL UNTUK MENINGKATKAN PENALARAN PESERTA DIDIK - Wulandari, Erlina Dwiyana; Marsitin, Retno; Fayeldi, Trija (Universitas Insan Budi Utomo, 2025)
Mathematics is one of the subjects that is considered difficult, boring, and the use of mathematics learning media in schools is still less than optimal due to limited media and time. This study aims to develop learning media based on local wisdom on snakes and ladders with valid, feasible, and effective question cards to improve students' reasoning. The study uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The instrument uses a validation sheet, a response questionnaire, and reasoning test questions. The developed media was tested in a limited field trial involving 6 students of class VIIA and a large field trial involving 25 students of class VIIB at SMP Diponegoro Tumpang. The validity was obtained from the validation results, the feasibility was obtained from the response questionnaire, and the effectiveness was obtained from the results of the students' reasoning test. The validation results showed very high validity. The feasibility results were very feasible, namely, in the limited field obtained a result of 3.79 and in the large field, 3.31 which means media. The effectiveness results were very effective, namely, the test question score in the large field test was 95.6%. Based on the research results, it can be concluded that the local wisdom-based learning media, snakes and ladders, developed is very valid, very feasible, and very effective for use in learning and can improve students' reasoning. It is hoped that the local wisdom-based learning media, snakes and ladders, with question cards, can be used in mathematics learning.